The aesthetic employment of sports in contemporary world painting - عادل سهم زباري; بان محمد علي (Basrah Arts Journal, 2026)
The current study (The Aesthetic Employment of Sports Games in Contemporary World Painting) addresses how the contemporary artist employed sports games as a subject of painting, what are the motives for beauty and stimuli in those games and the individuals who play them, and how the elements of beauty differ from one game to another. On this basis, the current study was launched, which included four chapters. The first chapter was devoted to the problem, which was summarized in the following question: How did the contemporary artist employ sports aesthetically in his works? It also presented its importance, need, limits and terminology. The second chapter included the theoretical framework, as it included two sections, the first entitled the historical dimension of sports games, and the second section entitled the impact of sports movements on global drawing. The third chapter contained the research procedures represented by the method, society, research tool and analysis of the research sample of three models. The fourth chapter included the results, their discussion, conclusions, recommendations and suggestions.